State-owned enterprises in Singapore: Historical insights into a potential model for reform - TAN, Cheng-Han (Institutional Knowledge at Singapore Management University, 2015)
This article argues that the Singapore GLC Model is so closely intertwined with Singapore’s idiosyncratic history and unique regulatory culture that, although the model has been extremely successful within Singapore, transplanting it to China could be difficult. The article also explores the extent to which the success of the Singapore GLC Model and China’s ambition to emulate it challenge notions that corporate governance systems are converging towards a market-oriented (American) model of the shareholder centric corporation and the extent to which the success of the Singapore GLC Model challenges the basic conception that private enterprise rather than the state is necessarily more efficient at allocating capital to its most productive use.